1975
DOI: 10.1111/j.1471-0528.1975.tb00592.x
|View full text |Cite
|
Sign up to set email alerts
|

PLASMA UNCONJUGATED 15α‐HYDROXYOESTRIOL (OESTETROL) LEVELS IN NORMAL HUMAN PREGNANCY

Abstract: Serial measurements were made of the concentration of plasma unconjugated oestetrol in normal human pregnancy. The mean curve and limits of normal variation have been established. Plasma levels rose from just below 2 ng/ml at 20 weeks to approximately 5 ng/ml at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The steroid hormones we have considered, differently from polipeptidic hormones, derive from different metabolic sources, even if both can give us useful indications about the well-being of the fetus-placental unity. In fact, we know that E 3 is sinthesized in the placenta from fetal precursors [21], while E 4 is mainly sinthesized in the fetal liver from placental precursors [13,22,29,31]. Therefore, we can't overlap the theoric value of these two parameters, but we have studied the possibility of compare these two assays s clinical parameters for testing the fetus-placental unity to have better informations about the well-being of the fetus [l, 18,29].…”
Section: Discussionmentioning
confidence: 99%
“…The steroid hormones we have considered, differently from polipeptidic hormones, derive from different metabolic sources, even if both can give us useful indications about the well-being of the fetus-placental unity. In fact, we know that E 3 is sinthesized in the placenta from fetal precursors [21], while E 4 is mainly sinthesized in the fetal liver from placental precursors [13,22,29,31]. Therefore, we can't overlap the theoric value of these two parameters, but we have studied the possibility of compare these two assays s clinical parameters for testing the fetus-placental unity to have better informations about the well-being of the fetus [l, 18,29].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to explain the above differences, since many factors can be involved, it is worth remembering that Korda et al (3) and Fishman and Guzik (1) both use an antiserum with a 2.5% cross-reaction with E3, resulting in an overestimation of about 10%, as the authors themselves observe. As far as total E4 is concerned, the present data are substantially in keeping with the single literature reference so far available (7).…”
Section: Discussionmentioning
confidence: 86%
“…Starting around week 30, the E 4 plasma levels increase substantially as pregnancy progresses [31,32]. One study reported 7-fold higher values at week 40 when compared to week 22-26 [33].…”
Section: Maternal and Fetal Estetrol Levels During Pregnancymentioning
confidence: 93%